(12-2y)/4=(18-4y)/2

Simple and best practice solution for (12-2y)/4=(18-4y)/2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12-2y)/4=(18-4y)/2 equation:



(12-2y)/4=(18-4y)/2
We move all terms to the left:
(12-2y)/4-((18-4y)/2)=0
We add all the numbers together, and all the variables
(-2y+12)/4-((-4y+18)/2)=0
We calculate fractions
(-2y)/()+(-((-4y+18)*4)/()=0
We calculate terms in parentheses: +(-((-4y+18)*4)/(), so:
-((-4y+18)*4)/(
We multiply all the terms by the denominator
-((-4y+18)*4)
We calculate terms in parentheses: -((-4y+18)*4), so:
(-4y+18)*4
We multiply parentheses
-16y+72
Back to the equation:
-(-16y+72)
We get rid of parentheses
16y-72
Back to the equation:
+(16y-72)
We get rid of parentheses
(-2y)/()+16y-72=0
We multiply all the terms by the denominator
(-2y)+16y*()-72*()=0
We add all the numbers together, and all the variables
(-2y)+16y*()=0
We get rid of parentheses
-2y+16y*()=0

See similar equations:

| 2x+7(×-7)=-4 | | 12-2y/4=18-4y/2 | | 3x+11=9x-5 | | 7(x-10)+4=5x-10 | | (8x+7)+(7x+53)=180 | | v+3/5=1/5 | | 8x+9x+16+7=40 | | 3+6-3v+4=1-2v-4v | | 12y-y=73 | | 13.75=2.5z | | 3z/7-4=0 | | 11x+5=60x+2 | | 4x+82=7x-5 | | Y-4-3y-6=-2y+10 | | 3x-5(x-3)=-2+3x-8 | | 8+3b=-16+1+7b+3 | | 42=6(q−88) | | -7y+5=-23* | | -5m-4+(-3)=14 | | 4s-30=34 | | 93+12x=96+12x-3 | | 6m-7=-43* | | (3y)-10=41 | | 4=24-4z | | (5x)/12=17/23 | | 6m-7=-43 | | 0.06(x+9)-1.24=0.08x | | 3n+24=-30/3 | | -1/2+1=1/2x-1 | | 0.06(x+9)-1.24=0.08 | | 15-4t=7 | | 16=2z+2 |

Equations solver categories